2008
DOI: 10.1186/1471-2199-9-27
|View full text |Cite
|
Sign up to set email alerts
|

Essential and distinct roles of the F-box and helicase domains of Fbh1 in DNA damage repair

Abstract: Background: DNA double-strand breaks (DSBs) are induced by exogenous insults such as ionizing radiation and chemical exposure, and they can also arise as a consequence of stalled or collapsed DNA replication forks. Failure to repair DSBs can lead to genomic instability or cell death and cancer in higher eukaryotes. The Schizosaccharomyces pombe fbh1 gene encodes an F-box DNA helicase previously described to play a role in the Rhp51 (an orthologue of S. cerevisiae RAD51)-dependent recombinational repair of DSBs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…We suspect that the balance between Fbh1 and Rad22 is critical to achieve appropriately formed Rad51 nucleofilaments, which are active yet not predisposed to aberrant behavior. Exactly how Fbh1 controls Rad51 activity is still not certain, although it is clear from the data presented here and elsewhere that its helicase/translocase activity is required (48,57). Fbh1 could act as part of a larger complex that controls Rad51 nucleofilament formation possibly through promoting the ubiquitination of target proteins (57).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…We suspect that the balance between Fbh1 and Rad22 is critical to achieve appropriately formed Rad51 nucleofilaments, which are active yet not predisposed to aberrant behavior. Exactly how Fbh1 controls Rad51 activity is still not certain, although it is clear from the data presented here and elsewhere that its helicase/translocase activity is required (48,57). Fbh1 could act as part of a larger complex that controls Rad51 nucleofilament formation possibly through promoting the ubiquitination of target proteins (57).…”
Section: Discussionmentioning
confidence: 97%
“…Exactly how Fbh1 controls Rad51 activity is still not certain, although it is clear from the data presented here and elsewhere that its helicase/translocase activity is required (48,57). Fbh1 could act as part of a larger complex that controls Rad51 nucleofilament formation possibly through promoting the ubiquitination of target proteins (57). Here its translocase activity might be used solely to localize the complex to sites where it is needed (e.g., blocked replication forks).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Fbh1 (F-box DNA helicase) is an F-box protein from S. pombe involved in the regulation of recombination levels and DNA repair (144,156,175). Like its human homolog, Fbh1 contains a helicase domain to unwind DNA.…”
Section: Fbh1: a Dna Repair F-box Proteinmentioning
confidence: 99%
“…This modification may regulate the substrate's function or target the substrate for proteasomal degradation 17 . Previous data derived from studies in S. pombe have suggested that both the F-box domain and the helicase domain of Fbh1 are required for the repair of DNA damage in that organism, although the helicase function seems more critical 18,19 . Moreover, genetic analysis suggested that yeast Fbh1 acts downstream of Rad51 in the HR pathway 18,20 .…”
mentioning
confidence: 99%